Modern Syntax : A Coursebook - Carnie, Andrew; Ebooks Corporation (Leiden : Cambridge University Press, 2011)
This practical coursebook introduces all the basics of modern syntactic analysis in a simple step-by-step fashion.
Description based upon print version of record.
Includes bibliographical references (p. 351-355) and index.
All age.
Keywords: Grammar, Comparative and general --Syntax.; Language and languages; Electronic books; Grammar, Comparative and general -- Syntax